Synthesis of molecularly imprinted polymers for nevirapine by dummy template imprinting approach - Weeranuch Kareuhanon (2018)
Nevirapine (NVP) and its structurally related analogs including nicotinamide (NAM), benzamide (BZM) and benzophenone (BZP) were used as templates in the synthesis of molecularly imprinted polymers for NVP. Molecular modeling was used to estimate binding energy of the complex formation between methacrylic acid (MAA) monomer and the selected templates, while equilibrium binding studies were applied to evaluate the polymer binding efficiency. The data indicated that NAM is the best candidate to prepare MIPs for retaining NVP due to a relatively similar binding energy between the NVP-MAA and NAM-MAA complex. The NAM-imprinted polymer showed a high binding affinity and selectivity toward NVP. When the polymer was applied as a sorbent in solid-phase extraction of NVP from human plasma, high recovery and reproducibility were obtained. © 2009 Vieweg+Teubner | GWV Fachverlage GmbH.